Consórcio entre milho e leguminosas, produção de palha e manejo do nitrogênio no feijão “de inverno” em região com verão chuvoso e inverno seco - Gerlach, Gustavo Antonio Xavier [UNESP] (2014)
The intercropping of green manures in maize can produce more dry matter of plants than in the single crop, which linked to the cultural remains of corn plants may benefit from the development and crop productivity in succession. Depending on the existing hind of trash in the area where is located the common beans crop in no tillage, nitrogen fertilizer there may be economy, especially in the case of the presence also of vegetables. Thus, the experiment was to evaluate the intercropping between maize and legumes in no tillage to produce mulch for the succeeding crop, evaluate its effect in common beans with application of rates of nitrogen and assess costs and profit from the system. The study was conducted in the experimental area of Faculdade de Engenharia de Ilha Solteira UNESP, located in Selvíria (MS) in the agricultural years 2011/12 and 2012 /13. The experimental design for maize was with randomized blocks with 4 replications and 10 treatments: maize, pigeonpea (Cajanus cajan), Crotalaria spectabilis and estilosantes (Stylosanthes capitata) in an exclusive crop; intercroping of maize + pigeonpea, maize + Crotalaria spectabilis, corn + estilosantes simultaneously seeded with corn, corn intercroping + pigeonpea, Crotalaria spectabilis + corn, corn + seeded estilosantes when maize plants were 5 leaves unfolded. The experimental design for the common beans was the randomized block in a factorial arrangement with 10x4 treatments consisted of cover crops and doses of nitrogen ( 0, 30, 60 and 90 kg ha-1 ) with 4 replications . It was concluded that the consortium with green manures had no effect on grain yield, and no increase in total dry matter after the corn harvest; was no influence of the corn crop residues and green manure on yield components and yield of common bean. The application rates of nitrogen positively influenced the dry matter of plants and common bean yield up to 90 kg ha-1. The greates ...